2023
DOI: 10.1002/rcr2.1240
|View full text |Cite
|
Sign up to set email alerts
|

X ‐linked inheritance of primary ciliary dyskinesia and retinitis pigmentosa due to RPGR variant: A case report and literature review

Aoi Kuroda,
Ho Namkoong,
Eri Iwami
et al.

Abstract: Bronchiectasis is a chronic respiratory condition characterized by irreversible bronchial dilation, often caused by infection or inflammation. It can be associated with primary ciliary dyskinesia (PCD), a hereditary disorder affecting cilia function in various organs and flagella. PCD's genetic heterogeneity leads to varying disease severity. PCD may be more prevalent in Asia, but its diagnosis is often delayed in Japan. This study reviewed a case of PCD and retinitis pigmentosa (RP) with the relevant literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A subsequent study in patients found significant ciliary depletion and goblet cell hyperplasia [59], and a recent report documents bronchiectasias in a Bardet-Biedl syndrome patient [60]. The association between retinitis pigmentosa and PCD, usually complicated with bronchiectasis, is well documented in the scientific literature [61]. A significant relationship between polycystic kidney disease and bronchiectasis have been observed, and one of the genes mutated in the ciliopathy, polycistin-1, is expressed in motile cilia in the airway epithelial cells [62,63].…”
Section: Concurrent Ciliopathies and Bronchiectasismentioning
confidence: 96%
“…A subsequent study in patients found significant ciliary depletion and goblet cell hyperplasia [59], and a recent report documents bronchiectasias in a Bardet-Biedl syndrome patient [60]. The association between retinitis pigmentosa and PCD, usually complicated with bronchiectasis, is well documented in the scientific literature [61]. A significant relationship between polycystic kidney disease and bronchiectasis have been observed, and one of the genes mutated in the ciliopathy, polycistin-1, is expressed in motile cilia in the airway epithelial cells [62,63].…”
Section: Concurrent Ciliopathies and Bronchiectasismentioning
confidence: 96%
“…Normal is more common. Kuroda A et al reported a case with a heterozygous RPGR variant and ODA+IDA defect on TEM [ 170 ].…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Patients with RPGR variants have rarely also been noted to have recurrent sinus, ear, and lung infections with the development of bronchiectasis but not laterality defects, with RPGR playing a role in both respiratory cilia and photoreceptor cilia [ 188 ]. TEM may have a normal appearance with abnormal motility on HSMVA, though some ultrastructural defects have also been reported [ 119 , 170 , 188 ].…”
Section: Genotype–phenotype Relationships In Pcdmentioning
confidence: 99%
“…Although some authors reported no respiratory symptoms in XLRP families and RPGR variants [ 11 , 12 ], other authors described the presence of PCD symptoms with motile ciliary defects in a variable number of males in XLRP families, indicating the incomplete penetrance of respiratory symptoms in those cases [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. McCray et al [ 20 ] observed a high percentage of XLRP patients with ciliary orientation abnormalities and disorganised ciliary beat, but without clinical consequences [ 20 ].…”
Section: Introductionmentioning
confidence: 99%